The consulting engineers : the British consulting engineers who created the world's infrastructure - Ferguson, Hugh, BSc; Chrimes, Mike (ICE Publishing, 2020)
This beautifully illustrated full colour book tells the full story of British consulting engineers for the first time. From their early beginnings, through the establishment of the profession in the 18th century, the `Railway Age' of the 1800s, their post-World War Two international boom and on to the recent commercialisation and consolidation of the industry. The authors, Hugh Ferguson and Mike Chrimes, bring their vast experience and expert subject knowledge to the book, tracking how an extraordinary group of engineers created the infrastructure of Britain, and of much of the rest of the world. The Consulting Engineers covers not just what consulting engineers do but also how their profession started and grew rapidly, and how the role has changed and continues to evolve.